Antibody persistence following meningococcal C conjugate vaccination in children and adolescents infected with human immunodeficiency virus - Ana Cristina Cisne Frota; Lee H. Harrison; Bianca Ferreira; Daniela Menna‐Barreto; Raquel Bernardo Nana de Castro; Giselle Pereira da Silva; Ricardo Hugo de Oliveira; Thalita F. Abreu; Lucimar G. Milagres; Cristina B. Hofer (Brazilian Society of Pediatrics, 2017)
Objective: HIV‐infected individuals (HIVI) are threatened by meningococcal infection and presented lower response to vaccines. Data are scarce on long‐term persistence of human serum bactericidal antibody (hSBA) after a meningococcal C conjugate (MCC) vaccine in HIVI youth; the authors aimed to describe this persistence in HIVI. Methods: HIVI and HIV uninfected individuals (HIVU), aged 2-18 years, CD4 >15% were recruited. Seroprotection (hSBA ≥1:4) at baseline and at 12-18 months after immunization was evaluated and the association of the different factors with the long‐term persistence was calculated using logistic regression. Results: A total of 145 HIVI, 50 HIVU were recruited and immunized, and their median age was 11 years (median age in HIVI group was 12 years, and 10 years in HIVU group, p‐value = 0.02). 85 HIVI (44%) had undetectable viral load (UVL). Seroprotection rate was 27.2%: 24.1% in HIVI and 36% in HIVU 12-18 months after immunization (p = 0.14). Baseline immunity (odds ratio [OR] = 70.70, 95% CI: 65.2-766.6); UVL at entry (OR: 2.87, 95% CI: 0.96-8.62) and lower family income (OR: 0.09, 95% CI: 0.01-0.69) were associated with seroprotection among HIVI. Conclusion: Seroprotection at 12-18 months after single dose of MCC was low for both groups, and higher among individuals who presented baseline immunity. Among HIVI, vaccine should be administered after UVL is achieved.